2022
DOI: 10.3390/foods11193064
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Characterization, Antioxidant, and Lipid-Lowering Effects of Yellow Mombin (Spondias mombin) Supplemented to Rats Fed a High-Fat Diet

Abstract: The aim of this study was to evaluate the effects of supplementing yellow mombin (YM) on the oxidative, somatic, and lipid parameters in rats fed a high-fat diet. A total of 24 adult Wistar rats were randomized into three groups: normal-fat diet (NF), high-fat diet (HF), and high-fat diet with YM supplementation (HFYM). Diets were administered for four weeks, and YM (400 mg/kg) was supplemented via gavage in the last two weeks of the experiment. After the four-week period, the somatic, serum biochemical, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…24,[51][52][53] Several researches have been done on the antioxidant efficacy of S. mombin. 24,54,55 A study evaluated the protective actions of the leaf and stem methanol extracts of S. mombin in rat model of carbon tetrachloride (CCl4)-induced hepatotoxicity. Pretreatment with 1000 mg/kg of the extracts markedly increased glutathione, catalase and superoxide dismutase levels.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…24,[51][52][53] Several researches have been done on the antioxidant efficacy of S. mombin. 24,54,55 A study evaluated the protective actions of the leaf and stem methanol extracts of S. mombin in rat model of carbon tetrachloride (CCl4)-induced hepatotoxicity. Pretreatment with 1000 mg/kg of the extracts markedly increased glutathione, catalase and superoxide dismutase levels.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…According to Table 1, carbohydrates are the major nutrient present in S. mombin fruit [18,48,49,56]. Concerning the organic acids, Lucena et al [24] identified acetic acid (3.34 ± 0.21 mg/g dw) and malic acid (6.00 ± 0.12 mg/g dw) in the S. mombin fruit.…”
Section: Nutritional and Mineral Compositionmentioning
confidence: 99%
“…Lucena et al [24] evaluate the effects of supplementing S. mombin (pulp and peel) on the oxidative, somatic, and lipid parameters of rats fed a high-fat diet. A portion of 400 mg/kg of body weight was supplemented via gavage for 14 days.…”
Section: Spondias Mombinmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [8] showed that administration of hydroxyl-α-sanshool, a long-chain unsaturated fatty acid amide extracted from Zanthoxylumbungeanum Maxim fruit (0.8 mg/kg for 28 days), improved the richness and diversity of gut microbiota, decreased the Firmicutes/Bacteroidetes ratio, and reduced glycosylated hemoglobin and diabetic dyslipidemia in streptozotocin-induced insulin resistance in rats. Lucena et al [9], investigating the functional properties of yellow mombin (Spondias mombin), showed that yellow mombin supplementation (400 mg/kg for two weeks) decreased dyslipidemia and oxidative stress in rats fed a high-fat diet. Cheng et al [10] developed an herbal formula consisting of three ingredients (bainiku-ekisu, black garlic, and Mesona procumbens Hemsl), named Mei-Gin formula.…”
mentioning
confidence: 99%